2022
DOI: 10.1111/and.14578
|View full text |Cite
|
Sign up to set email alerts
|

Fluted pumpkin seeds protect the spermatogenesis score index and testicular histology of caffeine treated rats

Abstract: The present study was designed to evaluate the protective effect of fluted pumpkin seeds (FPS) against caffeine (CAFF) induced testicular toxicity in rats. Thirty young healthy male Wistar rats (196 ± 12 g) were randomly organized into five sets of six animals per each group: control, caffeine (CAFF; 50 mg kg À1 bw) and FPS co-treatment groups (CAFF + 50 mg FPS, CAFF + 100 mg FPS and CAFF + 200 mg FPS kg À1 bw). CAFF and FPS were administered daily and twice per week respectively by oral gavage for 40 days. CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…The results obtained from histopathological examination showed that caffeine significantly affects the histology of the testes which was evidenced in the alteration of the normal architecture and integrity of the testes of the caffeine induced rats thereby resulting in the necrosis of spermatogenic cells (sertoli cells and the leydig cells). This is in agreement with the findings of Ezim and Abarikwu [18], they reported that CAFF decreased seminiferous epithelia thicknessand spermatogenesis score index and increased the number of tubules withabnormal histological features,This is in agreement with the findings of Bassey et al [14] and Ekaluo et al [15] The sertoli cells plays important roles in the overall development of the testes while the leydig cells are responsible for testosterone production and spermatogenesis. [19].…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained from histopathological examination showed that caffeine significantly affects the histology of the testes which was evidenced in the alteration of the normal architecture and integrity of the testes of the caffeine induced rats thereby resulting in the necrosis of spermatogenic cells (sertoli cells and the leydig cells). This is in agreement with the findings of Ezim and Abarikwu [18], they reported that CAFF decreased seminiferous epithelia thicknessand spermatogenesis score index and increased the number of tubules withabnormal histological features,This is in agreement with the findings of Bassey et al [14] and Ekaluo et al [15] The sertoli cells plays important roles in the overall development of the testes while the leydig cells are responsible for testosterone production and spermatogenesis. [19].…”
Section: Discussionsupporting
confidence: 91%
“…To normalize the tubular sections of testes to be measured, 50 round or nearly round seminiferous tubules per animal at × 100 magnifications were randomly selected and analyzed for each animal regardless of the stage of the seminiferous epithelium cycle as previously described (Abarikwu et al, 2019; Sasso-Cerri et al, 2017). In each tubular section, the number of seminiferous tubules with deranged epithelium and/or having sloughed germ cells in the lumen was quantified with Image J software (National Institute of Health, Bethesda, MA, USA), and the number of these atypical seminiferous tubules was recorded (Ezim and Abarikwu, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the histological features of the testes, 10 randomly chosen circular seminiferous tubules were selected, totalling 50 tubules per animal. In each tubular section, the number of tubules with desquamated germ cells in the lumen, degenerated epithelium, and clump of giant cells in the epithelium and inflammatory cells in the intertubular spaces were quantified and the numbers of these atypical seminiferous tubules and inflammatory cells were recorded and the mean calculated [ 37 ]. To assess the incidence of histopathologies in the liver, 50 digital images from 10 animals were analysed at × 400 magnification.…”
Section: Methodsmentioning
confidence: 99%